Variasi Fonologis Kosakata Bahasa Arab: Bahasa Arab Fushā dengan Bahasa Arab Maroko - Mashita Nadaa A. R; Sitie Fithriyah; Muhammad Irfan Fathurrahman; Rika Astari (Universitas Islam Negeri Palangka Raya, 2020)
This study aims to explore phonological variations between the Arabic vocabulary of fusha and Moroccan Arabic. This article uses a qualitative method with a literature approach in expressing phenomena that develop, especially in the aspect of phonological variation between Arabic fusha and Moroccan Arabic. The results of this study reveal that there are several phonological variations in the Arabic vocabulary of Fusha with Moroccan Arabic namely: (1) Sound reinforcement such as changes in low vowel sound / a / into moderate vowel sound / e /, (2) Lattice like weakening high vowel sounds / u / become a low vowel sound / a /, (3) Monophonization such as the merging of vowel sounds / a / and / u / into a single vowel sound / o /, (4) Dating which is divided into three categories such as anheresis (dating that occurs in some vocabulary such as aħmaru, azraqu, and asˤfaru become Ħmar, zraq, and sˤfar by removing the vowel / a / at the beginning of a word), syncope (some dating of vowel sounds in the middle such as / a /, vowel / u / and / a /, and vowel / i /, and apokope (The dating of the sound at the end such as the word ʃamsun becomes ʃams, and the word ħamma: mun becomes ħamma: m, the word baħrun becomes baħr by removing the sound / un / at the end of the word).